Unlocking strategic innovation - Datta, Surja, author.
1 online resource (1 volume
Keywords: "This new book explores how firms achieve competitive advantage in a disruptive, digital, and globalised business landscape. An integrative framework, 'The Four Rs of Competitive Success', is introduced, which covers the four core pillars of global strategy: resources and capabilities, technology and innovation (recombination), internationalisation and international markets (reach), and physical and virtual location (roots). It then explains how competitive advantage is achieved through an interaction of these four drivers against the backdrop of a globalised and digitised world. It is uniquely practical in its approach, combining theoretical understanding with international case studies and real-life examples throughout each chapter, including Apple, IKEA and Microsoft. Unlocking Strategic Innovation is concise, applied reading for postgraduate students studying international business, corporate strategy, innovation and digital strategy, as well as academics in the field. It should also be important reading for practitioners looking to gain further understanding of how firms compete and flourish in a global and technology-driven environment"--